Improving Learning Outcomes Of Big Ball Games Using Coopertive Methods In Primary Schools - Ramadhan Arifin; Mita Erliana; Ahmad Faisal (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study is the application of the cooperative learning model in order to improve the learning outcomes of big ball games in class III students of SDN 1 Landasan Ulin Tengah Banjarbaru. The method used in this study is a classroom action research method, namely the researcher as an observer. Observations at the time the teaching and learning process takes place. The subjects of this study were 27 students of class III (three) at SD Negeri 1 Landasan Uling Tengah Banjarbaru for the 2019/2020 academic year, consisting of 16 boys and 11 girls. The process of increasing the ability of learning outcomes in the manipulative motion material of big ball games by emphasizing the cooperative learning model, getting good results based on the predetermined KKM, which is 75. Defined results through cooperative learning model can improve student learning outcomes in motion manipulative big ball game with the following average: Observation of the first meeting was an average value of 70.1 The number of students who reached KKM 75 was 9 students with a percentage of 33.33% and the number of students who did not reach the KKM was 18 students with a percentage of 66.67% . and at the second meeting the average value was 85.5, the number of students who reached KKM 75 was 27 students with a percentage of 100% and the number of students who did not reach the KKM was 0 students with a percentage of 0% so this research was stopped at the second meeting (II).